Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 5505 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Lepidoptera", "Country is Japan", "Year is 1997" ] } The dataset includes 5505 records from 21 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0002319-150922153815467/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences